A review on natural fiber reinforced hybrid composites: chemical treatments, manufacturing methods and potential applications. (2021) - Prabhu, L.; Krishnaraj, V.; Sathish, S.; Gokulkumar, S.; Karthi, N.; Rajeshkumar, L.; Balaji, D.; Vigneshkumar, N.; Elango, K.S.
Abstract: Natural fiber reinforced composites are gaining more consideration by automakers and researchers to exploit in industrial applications due to lightweight, eco-friendly and sustainability. The aim of this paper is to provide an overview of natural fiber reinforced composites, effect of chemical treatments on natural fibers, manufacturing techniques and potential applications. The effects of various chemical treatments on natural fibers leads to altering the mechanical and thermal properties are studied. The applications of natural fibers reinforced composites are used in various industries such as automobile, aircraft, building, musical, sports and household applications are presented. The conclusion reveals that chemical treatment of the natural fiber enhances bonding between the fiber and matrix which ultimately improved the mechanical and thermal properties of the composites.